Editorial (Transactions of the Association of European Schools of Planning, 2019)
We are pleased to present the third issue of Transactions of the Association of the European Schools of Planning, the open-access, double-blind peer-reviewed journal of AESOP.The purpose of AESOP is promoting within Europe the development of teaching and research in the field of planning. Since its foundation it has always sought to foster the development of planning education, with the original AESOP Charter signed in Dortmund in 1987 placing a particular emphasis on this dimension of planning school activity. Reflecting this, the focus of the present issue of Transactions is on new experiences and issues in planning education. The papers presented here address a range of contemporary issues in the design and delivery of planning education in Europe and other parts of the globe. The focus of the contributions is diverse, ranging from wider structural and contextual issues such as the internationalisation of higher education, through to papers which report and reflect on, experiences of teaching in different institutions and contexts, and using different modes of delivery.